Associations of Metabolic Variables with Electrocardiographic Measures of Sympathovagal Balance in Healthy Young Adults - Millis, Richard M.; Hatcher, Mark D.; Austin, Rachel E.; Bond, Vernon; Goring, Kim L. (IntechOpen, 2012)
None